1984
DOI: 10.1111/j.1365-2265.1984.tb01394.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Dietary Calcium on Serum 1,25‐dihydroxyvitamin D Concentrations in Renal Stone Formers

Abstract: The role of 1,25-dihydroxyvitamin D (1,25(OH)2D) in the pathogenesis of idiopathic hypercalciuria was studied in 37 renal stone formers who, during two 10-day periods, followed first a normal and then a low calcium diet. The following samples were taken during each diet; 24 h urine; fasting blood and urine; blood and urine following a 1 g oral calcium load. Patients were divided according to serum calcium level, 24 h urinary calcium excretion on the first diet and fasting calcium excretion on the second diet. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…After full-text analysis, another 19 studies were excluded for the following reasons: 14 had no control group and no useful data, three did not provide standard deviations, and two reported duplicate data. Finally, 32 studies fulfilled our eligibility criteria and were enrolled in the meta-analysis [10,11,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47]. …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After full-text analysis, another 19 studies were excluded for the following reasons: 14 had no control group and no useful data, three did not provide standard deviations, and two reported duplicate data. Finally, 32 studies fulfilled our eligibility criteria and were enrolled in the meta-analysis [10,11,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47]. …”
Section: Resultsmentioning
confidence: 99%
“…Most studies clearly demonstrated that they ruled out hyperparathyroidism and/or renal tubule acidosis [10,11,18,19,22,26,27,29,33,34,36,43], some also excluded patients using calcium and/or vitamin D [18,26,29,35,39,42]. Seventeen studies described their criteria of hypercalciuria and they were not consistent [18,19,20,22,24,26,28,29,32,35,36,37,38,42,43,45], twelve of which defined hypercalciuria as urinary calcium excretion of more than 300 mg/24 h for men and 250 mg for women or 4 mg/kg/day [19,23,26,28,29,32,35,36,38,42,43]. The subjects were on a free or normal calcium diet in some studies [10,11,19,21,22,26,28,29,32,35,36,39,43], while restricted calcium diets were adopted in some others [24,27,…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the SMA analysis, no changes were observed in calcemia, phosphoremia (which was never diminished), Cr, or total proteins, except in patients with resorptive hy percalciuria. [26]. All these contradictory findings exacerbate the controversy over the metabolic processes involved in the hypercalciurias, making establishment of uniform criteria for their study a priority.…”
Section: Resultsmentioning
confidence: 99%